Reception of the « displacement » in The Arab critical discourse: كتاب "إشكالية المصطلح" لـيوسف وغليسي أنموذجا - Laouar, Imen; Bouceliou, Nabil (Journal of Human Sciences, 2023)
The critical term is considered one of the most important components of the creative text, because of its tuning of concepts and clarification of visions .. There is no doubt that it represents the pillar on which the critical discourse stands ...It has occupied, and still is, an important position among researchers and critics and has taken a significant amount of study and scrutiny through different generations. We preferred in this study to address the term « displacement » and to the problem of its multiplicity and the confusion of its transfer to the Arab world.